Exploring the Lived Experience of Parenting a Child with Developmental Dysplasia of the Hip. (3rd September 2021) - Wakely, Luke; Easey, Pollyanna; Leys, Jacqueline; Johnston, Catherine
Abstract: Aim: Parenting a child with a health issue such as hip dysplasia (DDH) can be complicated and stressful. We aimed to explore in depth, the lived experience of parenting a child with DDH. Methods: Guided by phenomenology of practice, six mothers and one father of children with DDH were engaged in semi-structured interviews about their parenting experiences. Data were audio-recorded, transcribed verbatim and analyzed thematically. Results: Two themes emerged. Surrendering the parenting prerogative, which described participants' accounts of losing parenting autonomy while needing to rely on others to meet the needs of their child. The second theme; Struggling to adjust day-to-day, described the impact that DDH had on parenting and how participants struggled daily to meet the needs of their child. Conclusion: The management of DDH impacted both the emotional and practical aspects of parenting. Health professionals are ideally placed to support the parenting of children with DDH, but need to understand the parents' particular needs to provide this support empathetically.